2021
DOI: 10.6004/jnccn.2021.0038
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Guidelines® Insights: Uterine Neoplasms, Version 3.2021

Abstract: The NCCN Guidelines for Uterine Neoplasms provide recommendations for diagnostic workup, clinical staging, and treatment options for patients with endometrial cancer or uterine sarcoma. These NCCN Guidelines Insights focus on the recent addition of molecular profiling information to aid in accurate diagnosis, classification, and treatment of uterine sarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 33 publications
2
115
0
1
Order By: Relevance
“…In a study of families with Lynch syndrome, the cumulative risk of EC by age 70 years was significantly higher among carriers of MLH1 mutations (54%), but this risk did not exceed 2% in women younger than 40 years of age [28]. As described in the National Comprehensive Cancer Network (NCCN-USA) guidelines for hereditary cancers, all women with EC should be genetically tested for MMR mutations, especially if diagnosed under 50 years of age, and if they are members of Lynch families [4].…”
Section: Fertility Sparing Treatments 21 Patients Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of families with Lynch syndrome, the cumulative risk of EC by age 70 years was significantly higher among carriers of MLH1 mutations (54%), but this risk did not exceed 2% in women younger than 40 years of age [28]. As described in the National Comprehensive Cancer Network (NCCN-USA) guidelines for hereditary cancers, all women with EC should be genetically tested for MMR mutations, especially if diagnosed under 50 years of age, and if they are members of Lynch families [4].…”
Section: Fertility Sparing Treatments 21 Patients Selectionmentioning
confidence: 99%
“…Medical treatment and uterine sparing management are now accepted as reasonable short-term alternatives to definitive surgical management in highly selected patients [4]. The fertility sparing treatment (FST) in EC includes hysteroscopic resection and/or curettage, in combination with hormonal therapy with progestin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1997, Kim et al first reported that 13 of 21 (62%) patients who were treated with progestin alone for type I EC had an initial response to progestins ( 5 ), beginning the exploration of the criteria for the conservative treatment. At present, relevant guidelines for fertility preservation treatment of EC have been launched, including the NCCN 1 ( 6 ), the Gynecological Oncology Committee of Chinese Anti-Cancer Association ( 7 ), and the European Society of Gynecological Oncology (ESGO) ( 8 11 ). The main indications agreed by the above guidelines/expert consensus are as follows: 1) Well-differentiated (grade 1) endometrioid adenocarcinoma confirmed by expert pathology review, 2) Disease limited to the endometrium on imaging, 3) Absence of suspicious or metastatic disease on imaging, 4) No contraindications to medical therapy or pregnancy, and 5) Patients should undergo counseling as the fertility-sparing option is not standard of care for the treatment of endometrial carcinoma.…”
Section: The Conservative Treatment Of Ecmentioning
confidence: 99%
“…HDR-VBT as the sole adjuvant post-operative radiation technique is currently considered the standard care for many subgroups of patients with early-stage disease [12][13][14].…”
Section: Introductionmentioning
confidence: 99%